1964
DOI: 10.1182/blood.v23.3.354.354
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Iron-Deficiency Anemia with Intravenous Iron Dextran

Abstract: Iron-dextran, in doses up to 3000 mg., was administered intravenously by single injection to 37 patients with iron deficiency and to 8 additional patients with acute gastrointestinal bleeding. No serious untoward effects were observed. One patient developed chills and mild abdominal cramps 8 hours after injection. Most of the iron could be accounted for in the circulating blood immediately after the injection. Iron was cleared from the plasma slowly for 3 weeks after the administration. Iron-dextran appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1965
1965
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…It was not until 1964 that the first publication on the use of parenteral iron appeared. 6 Thirty-seven patients in a pediatric hospital received a total dose infusion of HMW-ID. All responded.…”
Section: Iron Dextranmentioning
confidence: 99%
“…It was not until 1964 that the first publication on the use of parenteral iron appeared. 6 Thirty-seven patients in a pediatric hospital received a total dose infusion of HMW-ID. All responded.…”
Section: Iron Dextranmentioning
confidence: 99%
“…Experiences with the intravenous infusion of Imferon have been described lately (Basu, 1963;Gartlan, 1964;Lane, 1964;Powell, 1963) with a low incidence of generalized reactions of the type seen here, but with one fatality, according to the manufacturers, of an anaphylactoid nature. A varying degree of phlebitis has also been recorded, a complication reduced in frequency by Lane (1964) on decreasing the concentration of Imferon in the 5 per cent dextrose-water.…”
Section: Discussionmentioning
confidence: 68%
“…Additional Jectofer injections to replenish the stores to an equal degree would have taken another 6 days, a total time too long for in-patients. Basu (1963) Imferon, a method described by Wallerstein (1960) and Marchasin and Wallerstein (1964). These workers gave 2,000-3,000 mg. iron in single doses to 6 patients, and 250-1,000 mg. to 31 others, noting only one generalized and one local reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenously administered iron dextran has gained widespread acceptance as a safe and reliable method of correcting iron deficiency anaemia and replenishing body iron stores (Marchasin & Wallerstein, 1964;Bonnar, 1965 ;Will & Groden, 1968). Henderson & H i h i a n (1969) reported that the availability of a portion of these iron stores for erythropoiesis was reduced.…”
mentioning
confidence: 99%